Using Simulation in Training Pediatric Residents on Neonatal Abstinence Syndrome Scoring: An Experimental Study. (October 2020) - Agana, Marisha; Vos, Duncan; Williams, Mark; Baumgartner, Hans; Soares, Neelkamal
Abstract : Background: Neonatal abstinence syndrome (NAS) is characterized by significant physiological and behavioral signs involving multiple-organ systems in neonates following a prenatal exposure to opioids and other nonopioid drugs. Neonatal abstinence syndrome can result in serious morbidity, and even death, if unrecognized and untreated. The purpose of this study was to develop a simulation model of a standard video training of the Finnegan Neonatal Abstinence Scoring System (FNAS) and investigate the perceptions of comfort and competency of pediatric residents undergoing video or simulation training. Methods: Thirty-one pediatric and medicine-pediatric residents participated in this single-blinded randomized intervention study. The experimental group completed demonstrated simulation while the control group received the traditional video instruction. Both groups completed FNAS scoring on a case of a neonate with NAS. The FNAS scores of residents were compared with the scores of 2 expert raters. Pre- and posttraining and preference surveys were obtained from all participants. Results: Both experimental and control groups scored the FNAS scenario similarly and were also similar to the expert raters. Both groups also reported comparable levels of comfort and competency after the training, though first-year residents reported greater improvement than upper-level residents. The FNAS scores from expert raters were identical for the simulation and video scenarios. Implications for Practice: Although this study showed that a simulation training module can be used as a standardized teaching method to administer the FNAS, it can be cost-prohibitive and daunting to produce. Nursing professionals need to be aware of medical education training around FNAS due to the interdisciplinary nature of care for neonates with NAS. Institutions should consider implementing a diversity of practices and models with an interdisciplinary approach to training assessment of the neonate with NAS. Implications for Research: A more hands-on, less cost-prohibitive simulation training needs to be developed to teach FNAS administration with a broader range of professionals including interdisciplinary teams of nursing and medical professionals. Abstract : Supplemental Digital Content is Available in the Text.